Comparing 1-L and 2-L Polyethylene Glycol with Ascorbic Acid for Small Bowel Capsule Endoscopy: A Randomized Controlled Trial - Chang Kyo Oh; Sang Pyo Lee; Jae Gon Lee; Young Joo Yang; Seung In Seo; Chang Seok Bang; Yu Jin Kim; Woon Geon Shin; Jin Bae Kim; Hyun Joo Jang; Sea Hyub Kae; Gwang Ho Baik; et al. (Gut and Liver)
Background/Aims: Small bowel capsule endoscopy (SBCE) has become the standard for initial evaluation in the diagnosis of small bowel lesions. Although optimal visualization of the mucosa is important, patients experience difficulty in consuming a large volume of bowel preparation agents. This study aimed to compare the efficacy and safety of 1-L polyethylene glycol (PEG) with ascorbic acid (AA) and 2-L PEG with AA. Methods: In this prospective, multicenter, non-inferiority study, patients who received SBCE were randomly assigned to consume 1-L PEG with AA or 2-L PEG with AA for small bowel preparation. The primary outcome was adequate small bowel visibility quality (SBVQ). The secondary outcomes included diagnostic yield, cecal complete rate, and adverse events. Results: One hundred and forty patients were enrolled in this study, 70 patients per group. In the per-protocol analysis, there were no significant differences in the adequate SBVQ rate (94.0% vs 94.3%; risk difference, -0.3; 95% confidence interval, -8.1 to 7.6; p=1.000), diagnostic yield rate (49.3% vs 48.6%, p=0.936), or cecal complete rate (88.1% vs 92.9%, p=0.338) between the 1-L PEG with AA group and 2-L PEG with AA group. The incidence of adverse events did not differ significantly between the groups (12.9% vs 11.9%, p=0.871). Conclusions: One liter-PEG with AA is not inferior to 2-L PEG with AA in terms of adequate SBVQ for SBCE. One liter-PEG with AA can be recommended as the standard method for bowel cleansing for SBCE.